Application of Terrestrial Laser Scanning for the Inventory of Historical Buildings on the Example of Measuring the Elevations of the Buildings in the Old Market Square in Jarosław - Gardzińska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Terrestrial laser scanning (TLS) technology is increasingly used in surveying, construction and architecture. The potential of the data obtained by this method creates the possibility of its versatile application also in conservation and revitalization of monuments, archaeology or history. The use of this technology during the creation of architectural documentation of a historic building greatly facilitates the acquisition of comprehensive information about its actual condition in a fast, non-invasive and very precise manner.
Keywords: laser scanning; modelling methods; architectural documentation; 3D visualization; cultural heritage; skanowanie laserowe; modelowanie; dokumentacja architektoniczna; wizualizacja 3D; dziedzictwo kulturowe